REPRESENTASI KONTEKS AVATAR PADA LINGKUNGAN DINAMIS DIGITAL LIFE AT CAMPUS - , MUHAMMAD DEDI ISKANDAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Avatar is an object that represents a human user with the goal of reducing human workload in the virtual world, in a project named DILAC. Avatar is a context aware system that uses context as a trigger to activate its functionality. Context avatar has a dynamic form that needs to be modeled in a generic that can be applied in a variety of language activities scenario. The challenge of modeling context is a generic give a clear and complete definition of the mechanisms of context and context-based interaction models while still maintaining generisitas generated. The modeling is divided into two parts. The first section provides a definition of the concept of context and its relationship with the avatar, when the context of use, as well as the mechanisms that occur when the context of use. This modeling using a base framework with a formal language-based approach to ambient calculus and UNITY framework. Modeling both definitions apply to the interaction context consume information generated by the context . In modeling these interactions, the author used an object-oriented specification language Mocha towards a more implementable programming language. Context and context-based interactions have been modeled in accordance with the purposes of this study. It is expected that this model can be a guideline for the whole system, especially the developers of the program designers to implement the model in the design tools and models to add detail implementation of the system as needed.